Perception of Health Profession Students Towards Interprofessional Education at Hospital - Bella Alvina Lim; Yevri Zulfiqar; Laila Isrona (GLOBAL HEALTH SCIENCE GROUP, 2024)
Interprofessional Education (IPE) is a curriculum approach where students from various health profession backgrounds collaborate in one place to learn and get to know each other, as well as appreciate the role of each health profession to achieve collaboration and teamwork for the advancement of health services Objective: To determine the perception of health profession students towards interprofessional education at Unand Hospital Methods: This study is a descriptive research with a cross-sectional research design. The research was conducted at Unand Hospital with a total sample of 51 people consisting of 8 students of the Doctor Profession, 19 students of the Midwife Profession, 16 students of the Nursing Profession, and 8 students of the Pharmacist Profession. The research sample was determined using the proportionate stratified random sampling technique. This study uses an Interdisciplinary Education Perception Scale (IEPS) questionnaire. Results: A total of 40 students (78.4%) had a good perception of IPE with the highest percentage of competency and autonomy perception components (82.4%) and the perception component of understanding of other professions had the lowest percentage (62.7%). Nursing Profession students have the highest percentage of perception (87.5%), while Pharmacist Profession students have the lowest percentage of perception (62.5%). First-year students (83.3%) have a higher percentage of perception than second-year students (75.8%). Conclusion: The perception of health profession students towards IPE at Unand Hospital is mostly in the good category, however, the understanding of other professions is still lacking, so this needs to be considered and improved.